Manfaat Trancutaneus Electrical Nerve Stimulation Dan Massage Pada Kasus Cervical Root Syndrome Di Rsup Dr. Sardjito Yogyakarta - Janah, Miftakhul; , Agus Widodo, S.Fis, M.Kes (2016)
Backgraoud : Cervical Root Syndrome is a condition caused by irritation or cervical nerve root compression Symptoms are in the form of neck pain that spreads to the shoulders, upper arms and forearms, parasthesia and weakness or muscle spasm. Objective: To determine the benefits of the use of Trancutaneus Electrical Nerve Stimulation (TENS) and Massage on pain reduction, increasing strength bibs, increasing range of motion and increasing functional activity of the cervical spine. Results: After therapy 6 times showed a decrease in pain silent T0 : 2.0 to T6 : 2.0 , Tenderness T0 : 4.5 to T6 : 4.0 , Pain motion T0 : 5.5 into T6 : 4 , 5 , Improved LGS Flexion T0 : 12 to T6 : 14 Extensi T0 : 11 to T6 : 14 , Rotation decstra T0 : 16 to T6 : 17 , rotation of the left T0 : 16 to T6 : 17 Lateral Flexion decstra T0 : 15 to T6 : 17 The left lateral flexion T0 : 16 to T6 : 17 Increased functional activity using NDI get results T0 : 23 ( 46 %) to T6 : 14 ( 28 % ). Conclusion: Trancutaneus Electrical Nerve Stimulation (TENS) and Massage can reduce pain, increase muscle strength, increase range of motion, and increased functional activity of the cervical spine.